Dividing the Grey Divide: Deconstructing Myths About Older Adults’ Online Activities, Skills, and Attitudes - Quan-Haase, Anabel; Williams, Carly; Kicevski, Maria; Elueze, Isioma; Wellman, Barry (The American behavioral scientist (Beverly Hills), 2018)
Although research has demonstrated a grey divide where older adults are less involved and skilled with digital media than younger adults, by treating them as a homogenous group, it has overlooked differences in their digital skills and media use. Based on 41 in-depth interviews with older adults (aged 65+ years) in East York, Toronto, we developed a typology that moves beyond seeing older adults as Non-Users to include Reluctants, Apprehensives, Basic Users, Go-Getters, and Savvy Users. We find a nonlinear association between older adults’ skill levels and online engagement, as many East York older adults are not letting their skill levels dictate their online involvement. They engage in a wide range of online activities despite having limited skills, and some are eager to learn as they go. Older adults often compared their digital media use with their peers and to more tech-adept younger generations, and these comparisons influenced their attitudes toward digital media. Their narratives of mastery included both a positive sense that they can stay connected and learn new skills and a negative sense that digital media might overwhelm them or waste their time. We draw conclusions for public policy based on our findings on how digital media intersect with the lives of East York older adults.